3-(6-Bromohexyl)-1,5-dimethyl-1H-1,5-benzodiazepine-2,4(3H,5H)-dione - Dardouri, R.; Chahdi, F.O.; Saffon, N.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The seven-membered ring in the title compound, C17H23BrN2O2, adopts a boat-shaped conformation (with the C atoms of the fused-ring as the stern and the methine C atom as the prow). The bromohexyl substituent occupies an equatorial position, with the hexyl chain exhibiting an extended conformation. Weak intermolecular C-H center dot center dot center dot O hydrogen bonding is present in the crystal structure.